Analisis Dropship Jual Beli Online Profitable dalam Perspektif Ekonomi Syari’ah - Sutono Sutono; Rizaldy Ardiansyah (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
Dropshipping is essentially a buying and selling process between a seller and a buyer using the internet. Dropshipping is a product sale that allows dropshippers to sell goods to customers using photos from suppliers or stores and then sell them to customers at a price determined by the dropshipper. The questions to be answered through this research are: a) How does the buying and selling process work using a dropship system? b) How does the buying and selling process work using a dropship system from a sharia economic perspective. The method used in this research includes descriptive research with a qualitative approach. The data used are primary and secondary data obtained from verses of the Qur'an and the Hadith, books and journals, articles, and mass media, both print and electronic, related to the focus of the problem being studied in this research. The data analysis technique used in this research is the Miles and Huberman analysis model, using data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Samsarah contract is a solution to dropship transactions. The original law is permissible or permissible if carried out in accordance with Islamic provisions.